2013
DOI: 10.1371/journal.pone.0061506
|View full text |Cite
|
Sign up to set email alerts
|

Thy-1-Induced Migration Inhibition in Vascular Endothelial Cells through Reducing the RhoA Activity

Abstract: Our previous study indicated that Thy-1, which is expressed on blood vessel endothelium in settings of pathological and a specific of physiological, but not during embryonic, angiogenesis, may be used as a marker for angiogenesis. However, the function of Thy-1 during angiogenesis is still not clear. Here, we demonstrate that knock-down of the endogenous Thy-1 expression by Thy-1 siRNA transfection promoted the migration of human umbilical vein endothelial cells (HUVEC). In contrast, treatment with interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 34 publications
0
15
0
2
Order By: Relevance
“…We previously demonstrated that Thy-1 can serve as a marker for adult angiogenesis 13 . We also showed that expression of Thy-1 can inhibit endothelial cell migration, but did not affect endothelial cell proliferation 14 . In the present study, we used PMA as a Thy-1 inducer to further investigate how the Thy-1 expression is regulated.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…We previously demonstrated that Thy-1 can serve as a marker for adult angiogenesis 13 . We also showed that expression of Thy-1 can inhibit endothelial cell migration, but did not affect endothelial cell proliferation 14 . In the present study, we used PMA as a Thy-1 inducer to further investigate how the Thy-1 expression is regulated.…”
Section: Discussionmentioning
confidence: 61%
“…Previously, we demonstrated that Thy-1 can serve as a novel marker of adult, but not embryonic, angiogenesis 13 . We also demonstrated that overexpression of Thy-1 inhibited vascular endothelial cell migration and capillary-like tube formation through reducing the RhoA activity 14 . However, the molecular mechanism underlying Thy-1 up-regulation in vascular endothelial cells is still not clear.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Acredita-se que o CD90 está envolvido em vários processos celulares como proliferação, diferenciação, apoptose, adesão, e migração (Wen et al, 2013). O CD90 é expresso durante os processos de angiogênese fisiológica e patológica, mas não durante o desenvolvimento embrionário (Lee et al, 1998).…”
Section: Cd90unclassified
“…O CD90 é expresso durante os processos de angiogênese fisiológica e patológica, mas não durante o desenvolvimento embrionário (Lee et al, 1998). O aumento da expressão de CD90 em células endoteliais em cultivo inibe a adesão, migração e formação de tubos capilares, enquanto o bloqueio da expressão endógena de CD90 ocasiona a migração destas células (Wen et al, 2013).…”
Section: Cd90unclassified